Selected Decisions and Selected Documents of the International Monetary Fund, Thirty-Seventh Issue. (Selected Decisions; Thirty-Seventh Issue, 2014, 2014)
The Thirty-Seventh Issue of Selected Decisions and Selected Documents of the International Monetary Fund includes decisions, interpretations, and resolutions of the Executive Board and the Board of Governors of the International Monetary Fund, as well as selected documents to which frequent reference is made in the current activities of the Fund. In addition, it includes documents relating to the IMF, the United Nations, and other international organizations.